Alternative interpretations of grain-size data from Quaternary deposits - Mycielska-Dowgiałło, Elżbieta; Ludwikowska-Kędzia, Małgorzata (Geologos, 2012)
Several possibilities to present and to interpret the results of granulometric analyses of Quaternary ﬂuvial, aeolian, glacial and wash-out slope deposits were investigated. Attention is paid particularly to the cumulative curves at a pro-bability scale and the frequency curves, and it is shown how these curves can help to determine the sedimentary environment. The inclination of the cumulative curves in the part of the maximum proportion of a particular grain size appears signiﬁcant. It appears possible to obtain information on the density and dynamics of the transporting medium from the course of the cumulative curves (inclination and spread of grain size). The examination of textural parameters allows to draw regression lines characteristic of both deposits from various sedimentary environments and deposits from one single environment but with different histories as to their transport dynamics.